Fine particulate matter (PM2.5) exposure during a prolonged wildfire period and emergency department visits for asthma. Issue 1 (7th September 2015) - Haikerwal, Anjali; Akram, Muhammad; Sim, Malcolm R.; Meyer, Mick; Abramson, Michael J.; Dennekamp, Martine
Abstract: Background and objective: The 2006–2007 wildfire period was one of the most extensive and long lasting fires in Australian history with high levels of fine particulate matter (PM2.5 ). Large populations were exposed to smoke for over 2 months. The study aimed to investigate the association between wildfire‐related PM2.5 exposure and emergency department (ED) visits for asthma. Methods: A time‐stratified case‐crossover design was used to investigate associations between daily average PM2.5 and ED attendances for asthma from December 2006 to January 2007. ED data were obtained from the Victorian Emergency Minimum Dataset. Smoke dispersion during the wildfire event was modelled using a validated chemical transport model. Exposure data (daily average PM2.5, temperature and relative humidity) were modelled for the study period. Various lag periods were investigated. Results: There were 2047 ED attendances for asthma during the study period. After adjusting for temperature and relative humidity, an interquartile range increase in PM2.5 levels of 8.6 μg/m 3 was associated with an increase in ED attendances for asthma by 1.96% (95%CI: 0.02, 3.94) on the day of exposure. Lag periods up to 2 days prior did not show any association. A strong association was observed among women 20 years and older (5.08% 95%CI: 1.76, 8.51). Conclusions: Wildfire‐related PM2.5 was associated with increased risk of ED attendance for asthma during the wildfire event. It is important to understand the role of wildfire PM2.5 as a trigger for asthma presentations. Abstract : This time‐stratified case cross‐over study investigated the association between fine particulate (PM2.5 ) exposure from wildfire smoke and emergency department (ED) visits for asthma during the 2006–2007 wildfires in Victoria, Australia. Modelled air exposure data were used. Wildfire PM2.5 was associated with increased risk of ED attendance for asthma. See Editorial, page 6